The Cădariu-Radu Method for Existence, Uniqueness and Gauss Hypergeometric Stability of Ω-Hilfer Fractional Differential Equations - Aderyani, Safoura; Saadati, Reza; Fečkan, Michal (Mathematics (Basel), 2021)
Using the Cădariu–Radu method derived from the Diaz–Margolis theorem, we study the existence, uniqueness and Gauss hypergeometric stability of Ω-Hilfer fractional differential equations defined on compact domains. Next, we show the main results for unbounded domains. To illustrate the main result for a fractional system, we present an example.